PENGARUH PENILAIAN KEPRIBADIAN DAN KAPASITAS NASABAH TERHADAP PERSETUJUAN KREDIT DI PERUSAHAAN PEMBIAYAAN HOME CREDIT - Ratu, Tiffany Fransisca Heleni; Bagus Wiksuana, I Gusti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
During the Covid-19 pandemic in 2020, the Home Credit company has changed its credit acceptance scheme to adapt to current conditions. This is where every potential user of the Home Credit fintech application who wants to apply for credit requires an attachment regarding capacity. In addition to capacity, the Home Credit application also requires personal data as one of the guarantees for the proposed loan. The purpose of this study was to determine the effect of the personality of the prospective debtor on the approval of credit applications at the Home Credit financing company in the Denpasar city area and to determine the effect of the debtor's capacity on the approval of the loan application at the Home Credit financing company in the Denpasar city area. This research method uses quantitative data analysis techniques with multiple linear regression methods. The conclusion of the study is that there is a positive and partially significant effect between Personality on Credit Approval at Home Credit in Denpasar City and there is a partially positive and significant influence between Customer Capacity on Credit Approval at Home Credit in Denpasar City.